Pemberdayaan Petani dalam Peningkatan Kinerja Pertanian (Suatu Kajian dengan Pendekatan Teoritis) - R Sabrina (JASc (Journal of Agribusiness Sciences), 2021)
Farmer empowerment counseling in Improving Agricultural Performance is very influential on the economic sector, human resource development, and agriculture. This research discusses about competent human resources in agricultural development. The aim is to find out the benefits of development counseling and to produce human resources as competent agricultural development actors so that they are able to improve performance in agribusiness activities and the agricultural sector. The analytical method used in farmer extension is the communication method. The results show that there are many factors to improve agricultural performance and make competent human resources of farmers. The conclusion is agricultural empowerment counseling as a transfer of agricultural technology innovation to the community with village development efforts.